Communicating about computational thinking: understanding affordances of portfolios for assessing high school students' computational thinking and participation practices. Issue 2 (3rd April 2021) - Fields, Deborah; Lui, Debora; Kafai, Yasmin; Jayathirtha, Gayithri; Walker, Justice; Shaw, Mia
ABSTRACT: Background and Context : While assessment of computational thinking concepts, practices, and perspectives is at the forefront of K-12 CS education, supporting student communication about computation has received relatively little attention. Objective : To examine the usability of process-based portfolios for capturing students' communication about their computational practices regarding the process of making electronic textile projects. Method : We examined the portfolios of 248 high school students in 15 introductory CS classrooms from largely underserved communities, using a formal rubric (top-down) to code computational communication and an open-coding scheme (bottom-up) to identify computational practices described. Findings : Students demonstrated stronger abilities to communicate about computation using text than visuals. They also reported under-assessed CT practices like debugging, iterating, and collaborating. Students of experienced e-textile teachers performed substantially better than those with novice e-textile teachers. Implications : Portfolios provide a viable addition to traditional performance or survey assessments and meet a need to promote communication skills.